Promoting Innovation : The Differential Impact of R and D Subsidies - Cherif, Reda (IMF Working Papers; Working Paper, 2022)
We investigate the effect of R and D subsidies on firms' innovation by ownership, industry, and firm size using German firm-level data. The impact of R and D subsidies is heterogeneous across industries for multinational corporations (MNCs) and domestic firms while it does not differ substantially by firm size. Domestic firms have a larger response in R and D spending in low-tech manufacturing, knowledge-intensive services, and technological services while the response of domestic and foreign MNCs is broadly similar and is greater in medium-tech and high-tech manufacturing. Foreign MNC subsidiaries' response in terms of patents is greater than that of domestic MNCs in most industries.